Suboptimal Embryonic Incubation Temperature Has Long-Term, Sex-Specific Consequences on Beak Coloration and the Behavioral Stress Response in Zebra Finches - Choi, Madeline P.; Rubin, Alexander M.; Wada, Haruka (Frontiers in Ecology and Evolution, 2022)
Secondary sex characteristics, like beak color in some avian species, have indirect impacts on reproductive success, as they are considered to be honest indicators of condition, immunocompetence, and developmental history. However, little is known about the long-term effects of environmental perturbations on the production and maintenance of these secondary sex characteristics in avian species. In zebra finches (Taeniopygia guttata), redder beaks indicate increased carotenoid expression and implantation into beak tissue, and female zebra finches prefer males with pronounced bright red beaks as a mate. The present study examines the long-term effects of embryonic incubation temperature on the maturation of beak color in zebra finches. We also investigated the effects of embryonic incubation temperature on sensitivity to a handling and restraint stressor in adulthood. Specifically, the aims of this study were to examine: 1) whether suboptimal incubation temperatures affect the timing of beak color development and color characteristics before and after sexual maturity, 2) if repeated handling causes short-term changes in beak color and whether color changes are related to embryonic thermal environment, and 3) how thermal stress during incubation alters future responses to a repeated handling stressor. Zebra finch eggs were randomly assigned to one of three incubators: “Control,” “Low,” or “Periodic Cooling.” Beak color (hue, saturation, and value) was quantified before (45, 60, 75 days post-hatch (dph)) and after sexual maturity (95 dph), as well as after repeated handling stress later in adulthood (avg of 386 dph). We found that there were age- and sex- specific effects of incubation treatment on beak hue, where females from periodically cooled eggs had decreased hues (redder) in adulthood. Additionally, eggs laid later in a clutch had decreased beak saturation levels throughout life regardless of incubation environment. We found that females had lower beak hue and saturation following a capture and restraint stressor, while males showed increased beak saturation. Lastly, males subjected to the Low incubation treatment had relatively higher activity levels during restraint than those in the Control group. Overall, these findings suggest that fluctuating incubation temperatures combined with repeated, short-term stressors can have significant, sex-specific effects on sexual ornamentation and behavior.